Factors associated to the quality of life in children with epilepsy in a national hospital in Honduras - Gutierrez, Melba Zúniga; Romero, María Jose Flores; Cáceres, Fernando; González, Douglas Marlon Varela; Moncada, Martin Alfredo Medina (O Mundo da Saúde, 2023)
Epilepsy represents a large-scale problem that affects the social sphere of the patients who suffer from it. The following study aims to assess the quality of life of pediatric patients with epilepsy and to identify the factors associated with a lower quality of life. A cross-sectional, descriptive and analytical study was carried out in patients with clinical and electroencephalographic diagnosis of epilepsy, who attended the outpatient clinic of the neuropediatric service of the Teaching Hospital. A survey was administered, subdivided into data on the child, data on the parents or caregiver, type of epilepsy, treatment and the Quality of Life Scale for Children with Epilepsy (CAVE). The variables were analyzed using descriptive statistics and a multiple regression model to find predictors of quality of life. Of the 187 patients, 68 (36.4%) had a good quality of life. No significant gender differences were observed, nor in the overall score of the survey. Having fewer unmet basic needs (P=<0.0001) and not having refractory epilepsy were predictors of better quality of life (P=<0.0001). Parent-reported quality of life was mostly good or fair, having a higher number of unmet basic needs and being classified as having difficult-to-manage epilepsy were predictors of worsening quality of life as measured by the CAVE scale.